STUDI KOMPARATIF TENTANG IMPLEMENTASI SISTEM MANAJEMEN PENDIDIKAN DI SEKOLAH NEGERI DAN SWASTA (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The purpose of this research is to see the extent of the Comparative Study on the Implementation of Educational Management Systems in Public and Private Schools until now. The method of this research is that this study uses a qualitative approach with a comparative analysis method. Data was collected through interviews published in scientific journals and other mass media, observations related to government regulations, and the collection of documents from several public and private schools in various regions. The results of this study are that this comparative study shows that there are significant differences in the implementation of education management systems between public and private schools. Private schools tend to have greater flexibility in developing curricula, grading systems, and the use of technology, while public schools are bound by government regulations